2022
DOI: 10.7759/cureus.27086
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Analysis of Morphological Variations in Maxillary Second Molar in a North Indian Population Using Cone-Beam Computed Tomography

Abstract: Background: Cone beam computed tomography (CBCT) has evolved in the field of endodontics and has helped to diagnose and treat the case very easily and accurately. The researchers set out to pinpoint the exact placement of the roots and canals in the maxillary second molars of North Indians by analyzing CBCT pictures.Methods: In this study, in vivo CBCT was used to examine the maxillary second molars (n = 70) in detail. Both the number and configuration of root canals may be determined using Vertucci's categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, routine usage of this method should be avoided due to its higher cost and the need to justify the exposure to ionising radiation on an individual basis. 15,16 Utilising a dental microscope or surgical loupes aids in the diagnosis. These gadgets enhance the visibility of the surgical area, hence improving the chances of identifying hidden canals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, routine usage of this method should be avoided due to its higher cost and the need to justify the exposure to ionising radiation on an individual basis. 15,16 Utilising a dental microscope or surgical loupes aids in the diagnosis. These gadgets enhance the visibility of the surgical area, hence improving the chances of identifying hidden canals.…”
Section: Discussionmentioning
confidence: 99%
“…In 79% of cases, Pérez-Heredia et al 15 (Table 1) observed that maxillary second molars possessed three roots. Afzal N et al 16 (Table 1) also did a study specifically on maxillary second molars and found that the majority of these teeth had three roots. In their investigation, Ghoncheh et al 17 (Table 1) aimed to evaluate the root morphology of the maxillary first and second molars in an Iranian population.…”
Section: Search Methodologymentioning
confidence: 99%